ON or OFF?: Modulating the N-Methyl-D-Aspartate Receptor in Major Depression - Chan, Shi Yu; Matthews, Edward; Burnet, Philip W. J. (Frontiers in Molecular Neuroscience, 2017)
Since the discovery that a single dose of ketamine, an NMDA receptor (NMDAR) antagonist, had rapid and long-lasting antidepressant effects, there has been increased interest in using NMDAR modulators in the pharmacotherapy of depression. Ketamine’s efficacy seems to imply that depression is a disorder of NMDAR hyperfunctionality. However, studies showing that not all NMDAR antagonists are able to act as antidepressants challenge this notion. Furthermore, NMDAR co-agonists have also been gaining attention as possible treatments. Co-agonists such as D-serine and sarcosine have shown efficacy in both pre-clinical models and human trials. This raises the question of how both NMDAR antagonists and agonists are able to have converging behavioral effects. Here we critically review the evidence and proposed therapeutic mechanisms for both NMDAR antagonists and agonists, and collate several theories on how both activation and inhibition of NMDARs appear to have antidepressant effects.